On the Emotional Character of Trust - Lahno, Bernd (Ethical theory and moral practice, 2001)
Trustful interaction serves the interests of those involved. Thus, one could reason that trust itself may be analyzed as part of rational, goal‐oriented action. In contrast, common sense tells us that trust is an emotion and is, therefore, independent of rational deliberation to some extent. I will argue that we are right in “trusting” our common sense. My argument is conceptual in nature, referring to the common distinction between trust and pure reliance. An emotional attitude may be understood as some general pattern in the way the world or some part of the world is perceived by an individual. Trust may be characterized by such a pattern. I shall focus on two central features of a trusting attitude. First, trust involves a participant attitude (Strawson) toward the person being trusted. Second, a situation of trust is perceived by a trusting person as one in which shared values or norms motivate both his own actions as well as those of the person being trusted. As an emotional attitude, trust is, to some extent, independent of objective information. It determines what a trusting person will believe and how various outcomes are evaluated. Hence, trust is quite different from rational belief and the problem with trust is not adequately met in minimizing risk by supplying extensive information or some mechanism of sanctioning. Trust is an attitude that enables us to cope with risk in a certain way. If we want to promote trustful interaction, we must form our institutions in ways that allow individuals to experience their interest and values as shared and, thus, to develop a trusting attitude.